Controlled loading of paramagnetic gadolinium oxide nanoplates in PMAO-g-PEG as effective T1-weighted MRI contrast agents. Issue 15 (7th August 2014) - Yuan, Jiaquan; Peng, Erwin; Xue, Jun Min
Abstract